Rescuing Flavor Identity and Dynamic Perception in Pureed Dishes; a Restructuring Solution for the Puree Diet - Arancibia-Aguilar, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
With age, difficulties with masticating and swallowing means food consistency and structure must be modified, such as pureeing food. However, elderly consumers have reported that pureed food s taste lacks appeal. This study shows how pureeing food changes the recognition and dynamics of flavors and new strategies to improve them. Further, to measure the identification and dynamics of flavor, a new sensory method was investigated that combined Free Choice and Temporal Order of Sensation (Free-TOS). Three dishes (macaroni, pizza, and potato salad), their purees, and three pasta purees with added flavors (cheese and dry-cured ham; added directly or as an oil in water emulsion or using two types of emulsions (oil in water and water in oil) were assessed by three groups of 60 consumers using Free-TOS. Results showed that in the puree the frequency of mentioned sensations decreased compared with the dish, as it was more difficult to identify flavors. Adding flavors in powder form only allowed a cheese/ham flavor identification, but in the purees with emulsions, it was possible to identify the dry-cured ham flavor. Therefore, this study showed that the Free-TOS method does not need a predetermined attribute list and registers the actual identified flavors and their order of appearance.